2020
DOI: 10.1016/j.molliq.2020.113734
|View full text |Cite
|
Sign up to set email alerts
|

Impact of liquid lipid on development and stability of trimyristin nanostructured lipid carriers for oral delivery of resveratrol

Abstract: liquid lipids and future strategy for rational design of stable NLC systems for delivery of various bio-actives for drug delivery applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…However, the work of Pinto et al observed both an increase and a decrease, depending on the ratio of solid to liquid lipid and they highlight the importance of the ratio of saturated to unsaturated fatty acids [ 39 ]. Such differing results between experimental reports demonstrate the importance of careful design when specific properties are required but that varying the lipids, the ratios and the surfactant will all have an effect that can best be determined by a carefully executed DOE [ 32 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the work of Pinto et al observed both an increase and a decrease, depending on the ratio of solid to liquid lipid and they highlight the importance of the ratio of saturated to unsaturated fatty acids [ 39 ]. Such differing results between experimental reports demonstrate the importance of careful design when specific properties are required but that varying the lipids, the ratios and the surfactant will all have an effect that can best be determined by a carefully executed DOE [ 32 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The zeta potential of −25.6 signifies good stability of RV-NLCs due to electric repulsion. Our previous report has demonstrated good shelf-life stability of RV-NLCs [ 27 ]. In the presence of physiological media PSS, NLCs showed no disintegration or aggregation with zeta potential in the range of −9 mV due to the presence of an ionic layer on the surface of NLCs.…”
Section: Discussionmentioning
confidence: 99%
“…Blank (non-loaded), RV and RV–dye-loaded trimyristin–triolein NLCs were prepared using a hot melt emulsification technique [ 27 ]. The water phase containing surfactants, sodium cholate (0.25%) and Tween-80 (1%) was heated to 70 °C prior to amalgamation with the melted lipid phase comprising trimyristin (1.5%), triolein (0.5%), phosphatidylcholines (0.5%), Span-80 and RV (1 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LPH NPs (1 mL) were taken and centrifuged at 20,000 g for 2 h at 10 °C. For indirect method, supernatant was removed and was analyzed for free VRC content, employing a previously validated high-performance liquid chromatography (HPLC) method on a chromatograph (M/s Waters, USA) with acetonitrile and acetic acid solution (50:50) as mobile phase, at flow rate of 1 mL.minute −1 [ 32 , 33 ]. Further, the direct method involved the washing of pellet, thrice with water, and then dissolving it in 2% acetic acid solution and methanol, followed by probe sonication for 15 min and filtration through 0.4-micron syringe filter.…”
Section: Methodsmentioning
confidence: 99%